Preliminary Study on Nickel Nanoparticle growth by Sputtering Method - Lubis, Patricia; Latununuwe, Altje; Winata, Toto (Jurnal Dosen Universitas PGRI Palembang)
AbstractNickel nanopartickel has been grown on Si (100) substrate by the sputtering method. The growth parameters were 4 x 10-1 Torr pressure, 1500C temperature, 77,3 sccm Argon gas flow and 90, 30,10, 5, 1 minutes deposition time. The as deposited nickel nanoparticles were annealed for 30 minutes and 4 hours. The Nickel nanoparticles were then characterized using Scanning Electron Microscopy (SEM) and Energy Dispersive Analysis X-Ray (EDAX). The smallest size of Nickel nanoparticles found is about 50 nm.Keywords: nanoparticle, sputtering, anneal.